DISTRIBUTION OF RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM (RAAS) BIOMARKERS IN TREATED HYPERTENSIVE INDIVIDUALS FROM THE GENERAL POPULATION: THE CHRIS STUDY. (April 2021) - Foco, Luisa; Poglitsch, Marko; Gögele, Martin; Pramstaller, Peter Paul; Pattaro, Cristian
Abstract : Objective: Renin-Angiotensin-Aldosterone System (RAAS) is a critical target in hypertension management. However, direct quantification of angiotensin I (AngI) and II (AngII) is challenging due to compound instability, and was never attempted in large population-based cohorts before. Recently, a novel high throughput approach for molecular profiling of the circulating RAAS became available. We aimed at assessing AngI, AngII and aldosterone's distributions in individuals under anti-hypertensive drugs (AHDs) in a real-world setting. Design and method: We selected 500 participants under AHDs and 300 controls from the Cooperative Health Research in South Tyrol (CHRIS) study, a population-based study from an Alpine rural environment, defining age- and sex-matched groups (N = 100 each). Five groups included individuals under AHDs: (i) plain AngI-converting enzyme inhibitor (ACEi); (ii) ACEi+diuretic; (iii) plain AngII type 1 receptor blocker (ARB); (iv) ARB+diuretic; and (v) plain beta-blocker. Three were control groups: (vi) hypertensive without medication (vii) under non-AHDs, (viii) normotensive. Using RAAS Triple-A testing, a novel liquid chromatography combined with tandem mass spectrometry analysis, we simultaneously quantified aldosterone and equilibrium AngI and AngII, and used them to estimate markers of plasma renin activity (PRA-S pmol/L), ace-activity (ACE-S, [pmol/L]/[pmol/L]) and adrenal function (AA2-Ratio, [pmol/L]/[pmol/L]). Results: An evaluation of the first 240 analysed samples revealed specific molecular effects of AHDs, proving the performance of the approach. ACEi and ARB result in compensatory renin up-regulation: PRA-S median (interquartile range) was 54.6 (29.6–86.6) in the pooled controls, 77.4 (49.7–186.4) in ACEi, and 154.6 (55.2–600.4) in ARB (Kruskal-Wallis test p = 0.0001). Using ACEi was associated with suppression of ACE-S, whose median was 5.0 (4.2–6.4) in the pooled controls and 0.3 (0.1–0.6) in ACEi (p < 0.0001). Using ARBs resulted in AA2-Ratio suppression, with a median of 2.3 (1.4–3.9) and 0.7 (0.2–1.7) in the no-medication and ARB groups (p = 0.0001). Combining ACEi or ARB with diuretics was associated with further increase of PRA-S. Data did not support the hypothesis of different aldosterone levels (median = 101.7 pmol/L pooled sample) across groups (p = 0.179). Conclusions: Results point to a potential application of angiotensin-based biomarkers in class-specific drug monitoring, and will be further evaluated in the context of personalized treatment and therapeutic biomarkers.